Strategi Pengembangan Ubi Kayu di Kabupaten Serdang Bedagai - Salman Zuhry; Miftahuddin Miftahuddin; Azwana Azwana (Universitas Medan Area, 2018)
The Serdang Bedagai Regency chosen as the research site based on the grounds that the Serdang Bedagai Regency is an area of cassava production center of the second largest in North Sumatra. The formulation of problem in this study were : 1) describing the current state of cassava development in Serdang Bedagai Regency, includes the development of farming and processing industry, market prospects, potential and investment opportunities and policy support. 2) What are the external and internal factors that effect the development of cassava at Serdang Bedagai Regency. 3) What is the right strategy for the development of cassava at Serdang Bedagai Regency. This study uses observations with a research instrument by questionnaires and interviews to collect primary and secondary data. This research is descriptive. The are 5 respondents namely: Head of Department of Agriculture, Kasubdis Production, Agricultural Extension, Chairman of Farmers Group, and academics who were in the area of Serdang Bedagai Regency. Data analyzed using the SWOT analysis to find the right alternative strategies in order development of cassava as raw materials and processed food industry at Serdang Bedagai Regency. The research results obtained the alternative strategies of cassava development strategy priorities are: improve the quality of human resource farmers (STAS mean = 5,840 ), the cassava farmers establish cooperatives as a means of outreach, education, the introduction of technology and access to capital (average STAS = 5,777), conducting the education and training for farmers to increase their knowledge and mastery of technology (STAS mean = 5,774), utilizing the budget autonomy to increase cassava production so as to meet the needs of industry (STAS mean = 5,735), expanding the cassava growing areas (STAS mean = 5,673), the cooperation of the industry in the capital and marketing of cassava farming (STAS mean = 5,571), increasing the intensification of cassava farming in order quality can be competitive and profitable (STAS mean = 5,441), promoting the use of seedlings (clones) excel (STAS mean = 5,263). Keywords: strategic management, strategic factor, matrix IFAS, QSPM